Karen Armstrong’s perspective of compassion and its implications as a primary competency of teachers in Islamic education - Rahardja, Muhammad Nurfaizi Arya; Supriadi, Udin; Surahman, Cucu (Jurnal Iman dan Spiritualitas, 2025)
Compassion plays a crucial role in human life, particularly in education, where it helps shape positive character traits in children and enhances their altruistic behavior. This study aims to analyze Karen Armstrong's perspective on compassion as a core competency for educators in Islamic education. A qualitative research method with a descriptive-analytical approach was employed. The data sources include the primary source, Karen Armstrong's book Compassion: 12 Steps to a More Compassionate Life, and secondary sources such as relevant documents, scholarly articles, and other data. The research procedure was carried out in three steps: reviewing relevant references, collecting necessary references, and analyzing them according to the research objectives. The findings reveal that compassion, according to Armstrong, is the ability to place oneself in another person's position, to feel their suffering as if it were one's own, and to voluntarily engage in alleviating that suffering. In the context of Islamic education, compassion is a competency that every educator should possess. Educators who embody and implement compassion in their teaching activities can create a positive educational environment and foster constructive communication, thereby supporting the optimal development of children's character.